Pulsera inteligente: Watch Ur Health - Bravo Sánchez, Alejandro Gabriel; Camas Maay, Rodrigo Emanuel; Carrillo Fierros, Mariana Abigail; Cervantes Rodríguez, Raúl Fernando; Álvarez Cervera, María Margarita (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The COVID-19 disease continues to be a public health problem that society has integrated into its daily life. Prevention measures are a cornerstone to stop the growing increase in infections. Leading to an opportunity for technological development to create devices that contribute to the reinforcement of these measures. The "Smart Bracelet: Watch Ur Health" project is an innovative proposal for a device capable of warning its users from possible approaches of the hand to the face, which we know are a potential risk to get many infectious diseases, not limited only to COVID-19. This paper reports the development of facial approach detection algorithms and the implementation of a first prototype of the Smart Bracelet, integrating the functions of a common watch. Strategies are proposed for the improvement of functions in future developments.